Pengaruh Program Sentra Ternak Mandiri (STM) Terhadap Kesejahteraan Mustahiq Pada LAZ Ummul Quro Jombang - Fatmi, Dian Rahayu; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2019)
The distribution of zakat to the Sentra Ternak Mandiri (STM) Program to Mustahiq aims to have Mustahiq have a business so that it can improve the welfare of Mustahiq and also be able to change the status of Mustahiq to become Muzakki. This study aims to determine the effect of the Sentra Ternak M(STM) program on welfare mustahiq. This study uses a quantitative method with 15 mustahiq as respondents and data analysis techniques using SPSS 20. The test used in this study is a simple linear regression test, normality test, linearity test, and T test. The results of this study are the Sentra Ternak Mandiri (STM) program has an effect on welfare mustahiq.